Programmable logic controllers - Bolton, William (Libros electrónicos en Ebscohost, 2009)
A programmable logic controllers (PLC) is a real-time system optimized for use in severe conditions such as high/low temperatures or an environment with excessive electrical noise. This control technology is designed to have multiple interfaces (I/Os) to connect and control multiple mechatronic devices such as sensors and actuators.